Glucose revolution : the life-changing power of balancing your blood sugar - Inchauspé, Jessie (Simon & Schuster, 2022)
"Improve all areas of your health from your weight, sleep, cravings, mood, energy, skin, and even slow down aging, with easy-to-implement, science-based hacks to manage your blood sugar levels while still eating the foods you love. Glucose, or blood sugar, is a tiny molecule in our body that has a huge impact on our health. It enters our bloodstream through the starchy or sweet foods we eat. Ninety percent of us suffer from too much glucose in our system--and most of us don't know it. The symptoms? Cravings, fatigue, infertility, hormonal issues, acne, wrinkles... And over time, the development of conditions like type 2 diabetes, polycystic ovarian syndrome, cancer, dementia, and heart disease. Drawing on cutting-edge science and her own pioneering research, biochemist Jessie Inchauspé offers ten simple, surprising hacks to help you balance your glucose levels and reverse your symptoms--without going on a diet or giving up the foods you love... Both entertaining, informative, and packed with the latest scientific data, this book presents a new way to think about better health. Glucose Revolution is chock-full of tips that can drastically and immediately improve your life, whatever your dietary preferences"--Provided by publisher.